A sticky chocolate problem: Impression management and counter accounts in the shaping of corporate image. (December 2021) - Perkiss, Stephanie; Bernardi, Cristiana; Dumay, John; Haslam, Jim
Highlights: Producing chocolate comes with social, environmental and ethical problems. We argue that companies like Nestlé can use impression management to convey a positive public image of its operations. Cocoa producers like Nestlé deflect the use of child forced labour and unsustainable practices. Counter accounts act as performances to provide insight into corporate practices. CSR reporting and other disclosures fail to communicate a corporation's true operations and their impact. Abstract: Demand for chocolate is at an all-time high. However, producing chocolate comes with some sticky social, environmental and economic problems. This paper focuses on the issues of child labour, forced child labour and unsustainable farming practice within the chocolate industry, and specifically on the discourse about Nestlé's Ivory Coast cocoa supply chain. We analyse corporate disclosures, related counter accounts and subsequent responses in new and old media as a dynamic communication process. A mobilising of Goffman's (1959) dramaturgical metaphor of impression management contextualises each communication as a performance towards an audience. Behind the communications is Nestlé's need to repair its legitimacy – because child labour and unsustainable farming exist in its cocoa supply chain – and the audience's vested interests in their counter-performances. The Nestlé case offers substantive and nuanced insights into corporate disclosure and communication practices, how the Internet is changing the more unidirectional performances of the past, and how appreciation of counter accounts and subsequent responses to counter accounts contributes to theoretical understanding as well as provides insights into the plight of cocoa's child labourers.